Psychological flexibility in mild traumatic brain injury: an evaluation of measures. (29th July 2021) - Faulkner, Josh W.; Snell, Deborah L.; Theadom, Alice; Mahon, Susan; Barker-Collo, Suzanne; Skirrow, Paul
ABSTRACT: Primary objective: In this study, we examined the psychometric properties of measures of psychological flexibility in a mild traumatic brain injury (mTBI) sample. Method and Procedures: Adults who sustained a mTBI (n = 112) completed the Acceptance and Action Questionnaire – Acquired Brain Injury reactive avoidance subscale (AAQ-ABI (RA). Exploratory factor analysis and Rasch analysis were conducted to evaluate the facture structure, dimensionality, and differential item functioning. Construct validity was determined by correlating the AAQ-ABI (RA) with the Acceptance and Action Questionnaire-Revised (AAQ-II) and Fear Avoidance after Traumatic Brain Injury (FAB-TBI). Main outcome and Results: The AAQ-ABI (RA) was found to have strong internal consistency (Cronbach's α = 0.87). Consistent with previous findings, the AAQ-ABI (RA) had one distinct factor. Fit to the unidimensional Rasch model was adequate ( χ 2 (18) = 22.5, p = .21) with no evidence of differential item functioning across person factors examined. The AAQ-ABI (RA) also had expected relationships with theoretically relevant constructs. Conclusions: The AAQ-ABI (RA) appears to be a psychometrically sound measure of psychological flexibility in mTBI.